Workbook for the musician's guide to theory and analysis - Clendinning, Jane Piper; Marvin, Elizabeth West. (b, 2021)
This Workbook accompanies The Musician$1 (Bs Guide to Theory and Analysis, Fourth Edition, and features hundreds of exercises students can complete on tear-out-and-turn-in pages.s
Includes index.
Keywords: Music theory; Musical analysis